Fibromyalgia in rheumatoid arthritis: features of pain syndrome, impact on disease activity and quality of life of patients - N. A. Melikova; E. G. Filatova; A. M. Lila (Современная ревматология, 2022)
The prevalence of fibromyalgia (FM) in the general population is 2–8%, and among patients with rheumatic diseases it is 2–3 times higher. The presence of comorbid FM significantly affects the course of rheumatoid arthritis (RA).Objective: to assess the effect of FM on RA activity indicators, features of pain syndrome, and quality of life (QoL) of patients.Patients and methods. The study included patients with a confirmed diagnosis of RA. RA activity was assessed by the DAS28 index. FM was diagnosed according to the 2016 ACR criteria using the FM Diagnostic Questionnaire (FSQ). Patients also completed the central sensitization questionnaires – CS (CSI) and PainDETECT (PD). Pain intensity at rest was assessed using a visual analog scale (VAS, 10 cm), QoL was assessed using the FIQR and EQ-5D questionnaires.Results and discussion. 55 patients with RA were examined. FM was diagnosed in 24 of them (43.6%). RA activity in the presence and absence of FM (FM+ and FM- respectively) was high: the DAS28 index in the FM+ group averaged 4.58 points, and in the FM- group it was 5.14 points (p=0.227). The median pain intensity according to VAS in the FM+ and FM- groups was 6.5 and 4.0 cm, respectively (p=0.017). Symptoms of CS were more common in patients with FM than in patients without FM (p=0.004). The median score on the PD questionnaire in the FM+ and FM- groups reached 17.5 and 11.0 points, respectively (p=0.015). Patients with FM had lower QoL scores both in EQ-5D (p=0.037) and FIQR (p<0.001).Conclusion. FM is a serious burden for RA patients. The pain syndrome in the presence of FM is of greater intensity and prevalence, accompanied by neuropathic descriptors, which significantly worsens the quality of life in patients with RA.